Adult T-cell Leukemia/Lymphoma - Watanabe, Toshiki; Fukushima, Takuya (Springer Japan : Imprint: Springer, 2017)
This book provides essential information on the epidemiology, molecular and genetic features, anti-CCR4 antibody therapy and a nationwide study of transplantation on human T-leukemia virus type-I (HTLV-1) and adult T-cell leukemia/lymphoma (ATL). This rare but important disease has restricted endemic areas and distinct clinical features such as a high frequency of hypercalcemia, strong predisposition to infection and poor response to chemotherapy, aspects which set ATL apart from other types of non-Hodgkin lymphoma. Given the small number of patients, enrollment in clinical trials has not been feasible, and establishing treatment standard has been difficult but new evidence, such as results of nationwide studies on transplantation, have shown new insights and potential treatments. Based on recent evidence, the book presents new treatment methods for ATL and infection prevention of HTLV-1, enabling clinicians, researchers and post-docs specializing in hematology and virology to gain a valuable overview of the disease.